Numerical implementation of the MRC method for obstacle scattering problems - Gutman, Semion; Ramm, Alexander G. (My University, 2012)
The goal of this work is to show that the numerical solution of the obstacle scattering problem based on the MRC (modified Rayleigh conjecture) method is a competitive alternative to the BIEM (boundary integral equations method), and that it has numerical advantages which may be especially important in three-dimensional scattering problems with non-smooth domains, for example, with domains whose boundaries contain corners. The MRC is formulated, the algorithm based on it is described and numerical results are presented.
Keywords: Obstacle scattering; Modified Rayleigh conjecture; Numerical solution of obstacle scattering problem